2021
DOI: 10.1097/sla.0000000000004830
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 100 Patients More Than 4 Years After POEM for Achalasia

Abstract: Objective:We aim to describe the long-term follow-up data from our institution's POEM experience.Summary Background Data:Per-oral endoscopic myotomy (POEM) is a well-established endoscopic therapy for achalasia with excellent short-term efficacy, but long-term outcomes data are limited.Methods:Patients older than 4 years removed from POEM for treatment of achalasia were studied. Clinical success was defined as an Eckardt Symptom (ES) score ≤3 and freedom from reintervention for achalasia. Patients underwent es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…In particular, FLIP has demonstrated value for its real-time interpretation, which can be used at time of esophageal therapeutic intervention and to predict post-therapy outcomes. [48][49][50][51][52] It is expected that FLIP will have increasing prominence following the new emphasis placed on non-manometric data necessary to establish conclusive diagnoses of esophageal motility disorders in Chicago Classification v4.0. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, FLIP has demonstrated value for its real-time interpretation, which can be used at time of esophageal therapeutic intervention and to predict post-therapy outcomes. [48][49][50][51][52] It is expected that FLIP will have increasing prominence following the new emphasis placed on non-manometric data necessary to establish conclusive diagnoses of esophageal motility disorders in Chicago Classification v4.0. 6…”
Section: Discussionmentioning
confidence: 99%
“…Intra-operative FLIP has also been correlated to outcomes in POEM for achalasia. [48][49][50][51][52] Data from a retrospective single center study showed that patients who underwent intra-operative FLIP during POEM had significantly higher clinical success (Eckardt score ≤3) at follow-up compared to patients who did not have intra-operative FLIP (93% vs 81%, P < .05). 53 Furthermore, patients with type I and type II achalasia were more likely to have their myotomy extended if FLIP was used in order to achieve a DI > 2.9 mm 2 / mmHg, showing that the real-time data was incorporated into proceduralist decision-making.…”
Section: Utility Of Flip In Therapy For Esophageal Disordersmentioning
confidence: 99%
“…More recent studies suggest that the response to POEM may be durable as well. [1][2][3][4][5][6][7][8][9] Campagna et al evaluated the outcomes of POEM in 100 patients who completed ≥4 years of follow-up. 6 Clinical success was recorded in 88% and objective evidence of gastroesophageal reflux disease (GERD) found in one-third of cases on long-term follow-up.…”
Section: Long-term Outcomes Of Per-oral Endoscopic Myotomymentioning
confidence: 99%
“…In tune with previous studies, this present study confirms the feasibility and safety of POEM in esophageal motility disorders. 3,4,5 The primary objective of the study was to determine the long-term efficacy of POEM, defined as Eckardt score 3. The estimated clinical success was >95% at short-term (3 years) and >90% at midterm (4 years) follow-up.…”
mentioning
confidence: 99%
“…Although similar efficacy has been demonstrated in recent studies, the present study stands out in several aspects, including large numbers, prospective design, robust follow-up (98%), and objective evaluation of clinical efficacy with the use of the endoluminal functional lumen imaging probe (EndoFLIP; Medtronic, Minneapolis, Minn, USA) and barium emptying. 4,5 The response to POEM in patients with nonachalasia motility disorders, including jackhammer esophagus, distal esophageal spasm, and esophagogastric junction outflow obstruction, was relatively inferior with respect to Eckardt score in comparison with patients with achalasia. In previous studies, the response to POEM in patients with nonachalasia spastic esophageal motility disorders ranged from 80% to 90%.…”
mentioning
confidence: 99%